Pecularities of Adaptation of Anglicisms in Modern French in the Context of European Integration: Array - Starodiedova, Liudmyla (Journal of Danubian Studies and Research, 2020)
The article is devoted to the topical issue of adaptation of anglicisms into the French language. English, being one of the most spoken languages in the world, affects other languages more and more these days. English borrowings are used in almost all languages. A large number of anglicisms penetrated French in different periods of history. This process continues in various social spheres, including the field of new technologies.